Fabrication of thin solid electrolytes containing a small volume of an Li3OCl-type antiperovskite phase by RF magnetron sputtering. Issue 24 (4th November 2022) - Turrell, Stephen J.; Lee, Hyeon Jeong; Siniscalchi, Marco; Narayanan, Sudarshan; Pasta, Mauro; Speller, Susannah C.; Grovenor, Chris R. M.
Abstract : RF magnetron sputter deposition was performed using an Li2 O + LiCl powder target. The resulting solid electrolyte films were found to contain a small volume fraction of an Li3 OCl-type antiperovskite phase. Abstract : Several attempts to synthesize Li3 OCl – a lithium-rich antiperovskite compound envisaged as a potential solid electrolyte material for lithium metal batteries – have been reported, but few have yielded convincing results. There are two key challenges associated with this synthesis: the thermodynamic instability of Li3 OCl at room temperature and its extreme hygroscopicity. Therefore, the likelihood of inadvertently forming the structurally similar thermodynamically stable hydroxide halide compound Li2 OHCl is very high. In this report, we demonstrate the stabilization of a small volume fraction of antiperovskite phase with the characteristics expected for Li3 OCl in ∼0.5 to ∼1 μm films fabricated from a Li2 O + LiCl powder target by RF magnetron sputtering. Measures were taken to minimize the presence of moisture at all stages of synthesis and characterization. X-ray diffraction (XRD) experiments showed that reaction between the precursor phases occurred within the growing films to form a volume of antiperovskite phase with an identical lattice parameter to that predicted for cubic Li3 OCl. This antiperovskite phase decomposed into Li2 O and LiCl upon annealing at moderate temperatures. Characterization by Fourier transform infrared spectroscopy (FT-IR) confirmed the absence of O–H bonding in the films, providing further evidence that the antiperovskite phase was Li3 OCl rather than Li2 OHCl. Deposition of films with similar thicknesses from an Li2 OHCl powder target was also performed for comparison. While FT-IR results showed that O–H bonding was present in these films, a small volume fraction of an antiperovskite phase with identical lattice parameter to Li2 OHCl was only detected after heating the films to ∼100 °C. Owing to the low phase purities of films deposited from both target types, the Li + conductivities were found to be on the order of 10 −8 S cm −1 . For Li2 OHCl in particular, it is expected that further optimization of the processing conditions will lead to a significant increase in Li + conductivity. This is the first reported attempt to synthesize lithium-rich antiperovskite compounds by RF magnetron sputtering.